(NiSSLEDOWANIQ O {OPENE(B.s (NmONOGRAFIQs - (Nl(B. (NmAZELXs ((NmOSKWAs (NsA@Z kOMPOZITORs, 1971)
(Nw \TOT SBORNIK WKL@^ENY ^ETYRE RABOTY(B, (NOPUBLIKOWANNYE W RAZNOE WREMQ(B.s
Keywords: (NMONOGRAFIQs